Animal experimental implantation of an atrial septal defect occluder system. Issue 6 (1st December 1998) - Thomsen, A Bloch; Schneider, M; Baandrup, U; Stenbøg, E V; Hasenkam, J M; Bagger, J P; Hausdorf, G
Abstract : Objective: To establish the implantation technique for the atrial septal defect occluder system (ASDOS) device in an experimental animal model and to determine long term mechanical stability of the device and its in vivo properties in terms of biocompatibility and tissue reaction. Materials and methods: An atrial septal defect was created and the device implanted in 17 pigs (mean weight 30 kg). The implantation technique was refined and modified because of initial technical and anatomical complications during nine acute pilot studies. The technique proved to be feasible in eight subsequent survival studies. Four pigs were electively killed three months after implantation (group 1). The remaining four pigs were killed six months after implantation (group 2). Results: Necropsy showed all devices were embedded in soft tissue three months after implantation. Microscopic examination of atrial septal tissue showed an acute granulomatous inflammatory reaction in group 1 and fibrosis in group 2. The intensity of the inflammatory reaction around the device was clearly milder in group 2, indicating a decline in the inflammatory response with time. Clinical and biochemical investigations indicated acceptable biocompatibility of the device. Conclusion: The implantation technique for the ASDOS device in a chronic pig model has been established. Biocompatibility of the device was acceptable.